Utilization of both-side metal decoration in close-packed SnO2 nanodome arrays for ultrasensitive gas sensing - Shim, Young-Seok; Kim, Do Hong; Jeong, Hu Young; Kim, Yeon Hoo; Nahm, Seung Hoon; Kang, Chong-Yun; Kim, Jin-Sang; Lee, Wooyoung; Jang, Ho Won (ELSEVIER SCIENCE SA, 2015)
Metal decoration on hollow metal oxide nanostructures is an attractive route to enhance gas sensing properties. Herein, we present a facile method for the utilization of metal decoration on both the inner and outer surfaces of hollow metal oxide nanostructure for the first time. Close-packed SnO2 nanodome arrays decorated with Au nanoparticles are fabricated by soft-template method and self-agglomeration of an Au film. The position of Au decoration for SnO2 nanodome arrays is controlled by changing the deposition sequence of Au and SnO2 films. While inside, outside, and both-side Au-decorated SnO2 nanodome arrays show much higher responses to various gases than a bare SnO2 nanodome, it is shown that the response of both-side Au-decorated SnO2 nanodome arrays to C2H5OH at 300 degrees C is 18 times higher than that of the bare SnO2 nanodome arrays and the theoretical detection limit is below 1 ppb. These are attributed to the catalytic effect of Au nanoparticles on the modulation of barrier potentials in links between the individual SnO2 nanodomes. Our results demonstrate that the utilization of both-side metal decoration is an effective strategy for enhancing the gas sensing performance of hollow metal oxide nanostructures. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: OXIDE NANOSTRUCTURES; HOLLOW SPHERES; SENSORS; SENSITIVITY; CATALYSIS; DIAGNOSIS; FILM; H2S; NO2